Youth culture fashion in UP Diliman study of the clothing of selected student organizations - Caragay, Kristyn Taduran
The youth dominates the fashion world with their population as consumers who like to spend for clothing. They dress as a group and are influential as fashion leaders. To know their preferences and behavior in dressing will be helpful for the people in the clothing industry. This is a descriptive study on the fashion of the UP Youth Culture, wherein ten percent (105) of the university-recognized organizations from the academic, regional/provincial, special interest, cause-oriented, religious and sports and recreational clusters were observed and interviewed. The different organizations were observed to identify the clothing styles that they wear and distinguish the look that is unique to each of the group. An interview was also conducted to investigate the views of the members on their culture and their collective behavior and influences in clothing. Although the organizations insist on the diversity of their styles, a group look may be identified with such indicators as the way members carry themselves, their posture, the brads and the condition of specific articles of clothing they wear, and the way they accessorize. Common code among these organizations may be considered as The UP Youth Culture Fashion. The predominant pieces are jeans, shirt, and slippers or sneakers. They dress casually mainly to feel comfortable because of the environment and the weather of the campus. They also dress appropriately according to the activities and the events they participate in. Recommendations for further studies in the sociology of fashion, as well as recommendations for the fashion industry practitioners are included in this paper.